Penerapan Pembelajaran Berdiferensiasi Sesuai Gaya Belajar Siswa untuk Meningkatkan Keaktifan Peserta Didik Kelas IV - Nawang Wulan, Diah; Subekti, Ervina Eka; Alberta Budi Lestari (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The purpose of this study was to determine the increase in the activeness of fourth grade students through the application of differentiated learning according to students' learning styles. This mini-research is an experimental study with a quantitative method using the Pre-experimental Design type of One Group Pretest Posttest Design. The test was given twice, namely in the pretest and posttest which were used as data collection techniques. The data analysis techniques used were the normality test, the paired sample t-test, and the normalized gain test. This study was conducted in class IV B SDN Sawah Besar 01 Semarang with a sample of 28 students. The results of the data analysis obtained a value in the pretest normality test with a sig. 0.167 and in the posttest normality test a sig. 0.106 which means both are> 0.05 and are declared normal. Then in the paired sample t-test, the results showed that Ha was accepted, namely there was an increase in the activeness of fourth grade students through the application of differentiated learning that is in accordance with students' learning styles with a sig. <0.001. In the normalized gain test, a value of 0.4291 was obtained, which in the N score category, this value is included in the moderate category. So it can be concluded that students experienced a moderate increase in activity before and after the implementation of differentiated learning that is in accordance with students' learning styles.